Mapping the Relationship Between Enterprise Risk and Project Risks at Construction Company - Nurdiana, Asri; Wibowo, Mochammad Agung; Hatmoko, Jati Utomo Dwi (TEKNIK, 2025)
The construction industry is described as a project-based industry that inherently carries a wide range of risks. These risks are not only limited to projects but also extend to organizational or enterprise-level risks involving the company's directors, departments, and divisions. This study aims to examine the relationship between construction project risks and enterprise risks within construction companies. Specifically, it investigates how risks originating at the project level may influence or correlate with broader organizational risks, and vice versa. The research method involves analyzing secondary data, including project risk management reports and enterprise risk management documentation from construction firms. Through qualitative analysis, this study found a significant reciprocal relationship between project-level risks and company-level risks, which include the financial nature of the project risks, strategic risks, operational risks, and public & legal risks. These findings suggest that effective integration of project risk management (PRM) and enterprise risk management (ERM) is essential for enhancing overall risk resilience and organizational performance in the construction sector.